Malaysian public sector employees' financial preparedness and personal financial plan implementation - Abdul Rahim @ Abdul Wahab, Husniyah; Sabri, Mohamad Fazli (Malaysian Financial Planning Council, 2014)
A stable economic situation would minimize uncertainties in a longer time horizon. A stable economic situation and job security enable individuals to plan effectively for their future life. This study aims to determine the perceived financial preparedness of employees in the Malaysian public sector regarding their future needs based on age, differences in future financial preparedness and financial plan implementation based on each financial dimension among the identified financial adequacy groups. Multistage sampling based on states, departments and name lists was employed in this study resulting in 472 usable self-administered questionnaires. Slightly more than half of the respondents perceived their future financial preparedness was adequate based on their current personal financial preparation. Among those who perceived their financial preparation as adequate for their old age, financial preparedness tended to increase with age and all aspects of perceived future financial preparedness achieved scores above mean. This shows that the financially adequate respondents were confident that they were prepared in all aspects of financial preparedness. They were most confident about their preparation for health needs, expenses and emergency fund during their retirement or old age. Financially adequate respondents also saved more than the financially inadequate group, had better cash-flow, had more investments and subscribed to insurance for protection. Although public sector employees are supposed to be financially prepared for their old age through their present job security and pension scheme, they are still financially ill-prepared, especially the younger employees. This study suggests that early intervention programmes by employers and financial institutions would enable the potential ill-prepared to take advantage of the time value of money.